2009
DOI: 10.1080/02642060902793284
|View full text |Cite
|
Sign up to set email alerts
|

Cross-country comparison of intellectual capital performance of commercial banks in Asian economies

Abstract: This study explores the intellectual capital performances of commercial banks in eight Asian economies by applying Pulic's value-added intellectual coefficient method (VAIC). The results show that after controlling for the influence of loan quality (LQ), fund utilisation (FU), and Asian financial crisis, both physical and human capitals (HCs) are the main factors creating value for banks. From 1996 to 2001, banks in Hong Kong on average had the best intellectual capital performance while those in Thailand impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
62
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 25 publications
9
62
0
Order By: Relevance
“…A study conducted in Malaysia between 1997(Ting and Lean, 2009), which included financial institutions, showed that efficient use of IC correlated positively with ROA and profitability. In the banking sector, a study in eight Asian economies (Hong Kong, Indonesia, Malaysia, Philippines, Singapore, South Korea, Thailand, and Taiwan) between 1996 and 2001 identified IC among the main drivers of corporate performance regarding commercial banks (Young et al, 2009). The results show that human capital and capital employed were the main driving forces of value creation (i.e., measured by value added (VA)).…”
Section: Ic and Financial Performance In The Services Industrymentioning
confidence: 99%
“…A study conducted in Malaysia between 1997(Ting and Lean, 2009), which included financial institutions, showed that efficient use of IC correlated positively with ROA and profitability. In the banking sector, a study in eight Asian economies (Hong Kong, Indonesia, Malaysia, Philippines, Singapore, South Korea, Thailand, and Taiwan) between 1996 and 2001 identified IC among the main drivers of corporate performance regarding commercial banks (Young et al, 2009). The results show that human capital and capital employed were the main driving forces of value creation (i.e., measured by value added (VA)).…”
Section: Ic and Financial Performance In The Services Industrymentioning
confidence: 99%
“…It has also been applied to the banking sector for Poland by Śledzik (2013), in India by Narwal and Sushila (2015), for Islamic banks by Ousama and Fatima (2015) and for the Egyptian insurance market by Sherif and Elsayed (2016). Pulic (2004) himself as well as Nazari and Herremans (2007) have extended the model, Volkov (2012) has written a literary review on the model and its use and Young et al (2009) argue that the method can be used to describe the market value of a business much better than traditional financial indicators. Pulic (2008) also further examined the concept of intellectual capital efficiency and how VAIC TM can be used to study it.…”
Section: The Balance Sheetmentioning
confidence: 99%
“…IC has been classified into different components and measured by different methodologies [11,13,14,16,[22][23][24][25]. However, the advanced one, i.e., value-added intellectual coefficient (VAIC), developed by Pulic [24], is used in this study as a measurement of IC.Many studies have provided evidence regarding the relationship between IC and performance in different countries [4,18,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. However, evidence from financial institutions is still scarce.…”
mentioning
confidence: 99%